2018
DOI: 10.1155/2018/3986098
|View full text |Cite
|
Sign up to set email alerts
|

Soft Palate Pleomorphic Adenoma of a Minor Salivary Gland: An Unusual Presentation

Abstract: Approximately 10% of pleomorphic adenomas occur in the minor salivary glands with the palate being the most common site. Pleomorphic adenomas account for the majority of palatal tumours; however, minor salivary gland tumours have a higher risk of malignancy compared to tumours of the major salivary glands, so appropriate diagnostic evaluation should be prompt. We present a case of a 52-year-old man with a longstanding history of a soft palate pleomorphic adenoma which required excision under general anaestheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Case studies of huge soft palate PA have been previously reported. For instance Forde et al, reported a case of soft palate PA lesion measuring 9.9 cm in a 53‐year‐old male in the UK 9 . Murthy et al 13 described a case of large PA tumor in soft palate that was causing sleep apnea syndrome, while in their study, Yilmaz et al 14 described a case of a giant PA of soft palate leading to snoring and hypernasal speech.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Case studies of huge soft palate PA have been previously reported. For instance Forde et al, reported a case of soft palate PA lesion measuring 9.9 cm in a 53‐year‐old male in the UK 9 . Murthy et al 13 described a case of large PA tumor in soft palate that was causing sleep apnea syndrome, while in their study, Yilmaz et al 14 described a case of a giant PA of soft palate leading to snoring and hypernasal speech.…”
Section: Discussionmentioning
confidence: 99%
“…PA is the commonest tumor of both major and minor salivary glands with about 70%–80% of it occurring in the parotid gland. 9 , 10 , 11 It is a mixed tumor of the salivary glands derived from epithelial, myoepithelial, mesenchymal, and stromal elements. 5 The most common affected age groups are fourth to sixth decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local site recurrence is rare but has been described in cases with intraoperative tumor spillage or inadequate surgical resection. For inoperable cases, radiation therapy is employed [6].…”
Section: Introductionmentioning
confidence: 99%